Best practices for rehabilitation for older adults with dementia: Implementation of person‐centered care. (7th December 2020) - McGilton, Katherine S; Vellani, Shirin; Zheng, Nancy; Wang, Daniel; Yeung, Lydia; Escrig‐Pinol, Astrid
Abstract: Background and Objectives: Despite emerging evidence that older adults with cognitive impairment including those with dementia can be rehabilitated following a hip fracture, there is a paucity of research on strategies staff use and the support required to effectively rehabilitate this cohort. This qualitative study explores healthcare professionals' perspectives of providing rehabilitation for older adults with cognitive impairment. Methods: An in‐depth qualitative exploration of one site selected for its excellent outcomes in rehabilitation of older adults with cognitive impairment. Sixteen healthcare professionals with various backgrounds (occupational therapists, nurses, physiotherapists, and one social worker) were purposively sampled using a maximum diversity sampling strategy. Four focus groups were conducted to explore the experiences of professionals providing rehabilitation to this population. A hybrid inductive‐deductive approach was used to analyze the data. Results: Participating healthcare professionals acknowledged that older adults with cognitive impairment deserved a chance at inpatient rehabilitation and favourable outcomes were achievable; however, their knowledge, skills, and attitudes required reframing. Analysis identified three essential components to rehabilitating this cohort: i) staff's need for education, mentorship, and support to facilitate positive outcomes for persons with dementia, as well as for the healthcare team ; ii) the importance of knowing each patient to individualize rehabilitation approaches that encourages participation in rehabilitation; and iii) the need for care partner involvement by making contributions to rehabilitation care while in the hospital as well as continue to support recovery when they returned home, with support and education from the rehabilitation staff. Conclusions: Rehabilitation of older adults with cognitive impairment is achievable and healthcare professionals can learn how to modify their practices to achieve positive patient outcomes. However, support and involvement of management to help create a vision for success is essential.